MODALITY IN THE DISCOURSE OF FOOTBALL MANAGER 2007 GAME TEXTS (TEXT ANALYSIS USING MODALITY OF FUNCTIONAL GRAMMAR) - FERNANDO, Virgo (2008)
This study entitled "Modality in the Discourse of Football Manager 2007 Game Texts (Texts Analysis Using Modality of Functional Grammar)". The study aims to investigate the answer of these following questions: 1) What are the types of modality that occur in the FM'07 game text? 2) How does the use of modality reveal the relations between characters in the FM'07 game text? The focuses in this research are modality occurrences in the news screen within the game. The data of this paper was collected by retyping the texts that occur news screen within the game. Two main characters i.e. chairman and physiotherapist utterances were taken from the retyped texts. In the step of analyzing the data, the writer employed the Fairclough's critical discourse analysis (CDA) framework divided into three steps: identifying, classifying and interpreting the occurrences of modality. Halliday's theory of modality, i.e. type of modality, system of modality value, and modality orientation is used as tools to identify, classify and interpret the occurrences. In the view of modality types, the data shows: probability occur 45 times, usuality occur three times, obligation occur five times, and inclination occur 14 times. In the view of modality value, the data shows: high value modality occur 3 times, medium value modality occur 61 times, low value modality occur 3 times. The occurrences of all four types of modality with the values attached within them by the chairman signify the chairman has the ability to state and modalize his opinion by the use of probability and usuality. The chairman also in a position that is able to request others characters to perform some actions through the use of obligation. Furthermore, the occurrences of inclination expressed in the chairman's utterances indicate the chairman's social status as the character that has the ability to perform some action for other's characters. The limited use of type of modality within the physiotherapist initiates the physiotherapist is placed as the characters that only able to give opinion. It's evidenced that the use of modality differentiates characters' social status. It can further be said that there is a hierarchy in the world including in a relatively egalitarian society such as Western world. We are expected to behave accordingly.